Gone corporate? The changing face of entrepreneurship in contemporary universities. (24th August 2010) - Vorley, Tim; Nelles, Jen
Universities are widely cited as engines of the knowledge economy, with public policy increasingly viewing universities as integral to economic growth and competitiveness. This new function, colloquially known as the Third Mission, has seen the entrepreneurial role of universities emphasised by government and institutional policy, although seemingly presents entrepreneurship as a one-dimensional process. We argue that the prevailing focus of policy has seen a shift in the nature of entrepreneurship and distinguishes between academic entrepreneurship as an individual pursuit and university entrepreneurship as institutionally led. The paper then considers how the formalisation of the Third Mission has resulted in the institutionalisation of entrepreneurship and contends that the corporate entrepreneurship literature can serve as lens to better understand the entrepreneurial turn in academe. The paper concludes by identifying the scope for corporate entrepreneurship to contribute to understanding and (re)conceptualising the nature of entrepreneurship in higher education.